‘These four letters s o l a are not there’: Language and Theology in Luther's Translation of the New Testament - Methuen, Charlotte (Studies in church history, 2017)
Luther's 1522 translation of the New Testament is one of the most significant translations in Christian history. In it, he offers a translation of Romans 3: 28 which introduces the word allein: ‘So halten wir es nun, daß der Mensch gerecht werde ohne des Gesetzes Werke, allein durch den Glauben.’ As Luther himself recognized in his Open Letter on Translating (1530), the word ‘alone’ does not appear in either the Greek text of Romans or the Vulgate; nor do other contemporary vernacular translations include it. Luther asserted that the introduction of the word allein arose from his attention to the German language. This claim has often been regarded as specious, since the introduction of allein serves to underline a key aspect of Luther's theology, namely his doctrine of justification by faith. This article examines Luther's translation practice, and particularly his comments on Romans 3: 28 in his lectures on Romans, his preface to Paul's epistle to the Romans and other writings, concluding that Luther was indeed concerned to produce a fluent and coherent German translation of the biblical text, but that he wished also to produce one that was theologically unambiguous. Not only linguistic considerations, but also Luther's theological priorities, and his definition of theological unambiguity, determined his definition of a good translation.